LITERASI MEDIA DI ERA POST TRUTH - Bambang Mudjiyanto; Amri Dunan (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2020)
AbstractFraming of media messages through text, sound and images is a media activity to influence the thoughts and feelings of the audience. The relationship between media and audiences is built by media messages, whereas media messages are in themselves unique. Media literacy is intended to make media literate individuals who have an understanding and skills in access to, knowledge, and attitudes towards the media used. Media literacy is built to increase individual control over the media they use to send and receive messages. This social shift cannot be separated from the influence of the strengthening of the digital world where humans are connected to one another in a network called the internet. This condition makes information production no longer a monopoly on mainstream media but also social media managed by the public. The emergence of hoax news on social media, the post truth era is marked by media and journalism indecision, especially in dealing with fake statements from news sources. Post truth is an abnormality. Adapted societies, of course, still adhere to the values of truth and divine morality as shared values.Keywords: Literacy, Media, Post TruthAbstraksiPembingkaian pesan media melalui teks, suara dan gambar merupakan aktivitas media untuk mempengaruhi pikiran dan perasaan khalayak. Hubungan antara media dan khalayak dibangun oleh pesan media, sedangkan pesan media itu sendiri sesuatu yang khas. Literasi media dimaksud bertujuan menjadikan individu melek media yang memiliki pemahaman dan kecakapan atas akses, pengetahuan, dan sikap terhadap suatu media yang digunakan. Literasi media dibangun untuk meningkatkan kontrol individu terhadap media yang mereka gunakan untuk mengirim dan menerima pesan. Pergeseran sosial tak lepas dari pengaruh menguatnya dunia digital dimana manusia terkoneksi satu sama lain dalam jaringan bernama internet. Kondisi ini membuat produksi informasi tidak lagi menjadi monopoli media arus utama (mainstream) melainkan juga media sosial yang dikelola oleh masyarakat. Munculnya berita-berita hoaks di media sosial, era post truth ditandai dengan kebimbangan media dan jurnalisme khususnya dalam menghadapi pernyataan-pernyataan bohong sumber berita. Post truth adalah sebuah ketidaknormalan. Masyarakat beradap, tentu masih berpegang pada nilai-nilai kebenaran dan moralitas ke-Tuhan-an sebagai nilai bersama.Kata-kata Kunci: Literasi, Media, Post Truth